Ecological and genetic evidence for cryptic ecotypes in a rare sexually deceptive orchid, Drakaea elastica. (18th December 2014) - Menz, Myles H. M.; Phillips, Ryan D.; Anthony, Janet M.; Bohman, Björn; Dixon, Kingsley W.; Peakall, Rod
<x xml:space="preserve">Abstract</x> Species with specialized ecological interactions present significant conservation challenges. In plants that attract pollinators with pollinator‐specific chemical signals, geographical variation in pollinator species may indicate the presence of cryptic plant taxa. We investigated this phenomenon in the rare sexually deceptive orchid Drakaea elastica using a molecular phylogenetic analysis to resolve pollinator species boundaries, pollinator choice experiments and a population genetic study of the orchid. Pollinator choice experiments demonstrated the existence of two ecotypes within D. elastica, each attracting their own related but phylogenetically distinct pollinator species. Despite the presence of ecotypes, population genetic differentiation was low across populations at six microsatellite loci (FST = 0.026). However, Bayesian STRUCTURE analysis revealed two genetic clusters, broadly congruent with the ecotype distributions. These ecotypes may represent adaptation to regional variation in pollinator availability and perhaps the early stages of speciation, with pronounced morphological and genetic differences yet to evolve. Resolution of the taxonomic status of the D. elastica ecotypes is required as this has implications for conservation efforts and allocation of management funding. Furthermore, any reintroduction programmes must incorporate knowledge of ecotype distribution and pollinator availability to ensure reproductive success in restored populations. © 2014 The Linnean Society of London, Botanical Journal of the Linnean Society, 2015, 177, 124–140.